Advances in Ergonomics in Design Proceedings of the AHFE 2017 International Conference on Ergonomics in Design, July 17−21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA - Rebelo, Francisco; Soares, Marcelo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book provides readers with a timely snapshot of ergonomics research and methods applied to the design, development and prototyping - as well as the evaluation, training and manufacturing - of products, systems and services. Combining theoretical contributions, case studies, and reports on technical interventions, it covers a wide range of topics in ergonomic design including: ecological design; educational and game design; cultural and ethical aspects in design; user research and human-computer interaction in design; as well as design for accessibility and extreme environments, and many others. The book places special emphasis on new technologies such as virtual reality, state-of-the-art methodologies in information design, and human-computer interfaces. Based on the AHFE 2017 International Conference on Ergonomics in Design, held on July 17-21, 2017, in Los Angeles, California, USA, the book offers a timely guide for both researchers and design practitioners, including industrialdesigners, human-computer interaction and user experience researchers, production engineers and applied psychologists.
A preventive ergonomic approach based on virtual and immersive reality -- Improving the design of virtual reality devices applying an ergonomic guideline -- Virtual reality self-induced motion sickness: An exploratory study -- Comparing three stimulus presentation types in a virtual reality experiment to study the route-choice of users during an emergency situation -- Methods and procedures for usability testing in virtual reality systems -- Eye tracking-based reverse inference approach for design of restaurant information display -- Ergonomics evaluation of a manual braking system for skateboards -- Improving HMI of vehicle exterior design using adaptive structures -- Ergonomic/human factors in the design process: Methodological tool for context characterization and analysis of accessibility -- Evaluation of macro-ergonomic methods for the application of organizational analyzes in start-ups -- Design and development of bionic hand prosthesis -- Modularity and variety in the customization of functional clothes for people with disabilities -- A study exploring the ergonomic facets in ethnic products -- Comparison of anthropometric data for the design of chairs between seven countries -- Segmentation of anthropometric data of the Brazilian female population. .
Keywords: Computational intelligence; Engineering design; User interfaces (Computer systems).; Human-computer interaction; Cognitive psychology; Manufactures; Computational Intelligence; Engineering Design; User Interfaces and Human Computer Interaction; Cognitive Psychology; Machines, Tools, Processes